(untitled) (Bunayya : Jurnal Pendidikan Anak, 2025)
The importance of classroom management strategies in supporting slow-learning children in early childhood education is a particular concern. Therefore, the purpose of this study is to analyze the classroom management strategies implemented by teachers for slow-learning children at Muhammad Fahri Kindergarten. The method used is a qualitative method with a case study approach, while the data collection technique is through field observation and in-depth interviews with 1 class teacher. The results of the study indicate four main strategies in classroom management, namely establishing a learning environment in accordance with the principle of the least restrictive environment, building a conducive learning atmosphere through a scaffolding approach and social support, providing flexible learning time to accommodate the child’s speed of understanding, and the use of visual and concrete learning media to facilitate understanding of the material. These strategies have been proven to help slow-learning children be more focused, motivated, and confident in participating in learning. The findings of this study emphasize the importance of a different and inclusive approach in classroom management in early childhood learning activities, especially for slow-learning children so that it can be a deep consideration for educators.